Introduction : : the role of nature in the Anthropocene - Höfele, Philipp; Müller, Oliver; Hühn, Lore (2022)
Abstract: In a paradigmatic selection, the Special Issue unites contributions from biology, sustainability research, psychology and philosophy as well as media science and literary studies. It aims to discuss to what extent and on what basis the concept of nature is treated in the Anthropocene discourse with new perspectives, intentions and narratives. Not only the possibly changed conditions for a definition of nature in the Anthropocene are questioned, but also the necessity of an inter- and transdisciplinary opening, which goes along with this questioning and its connection with theoretical and practical issues